2017
DOI: 10.1371/journal.pone.0176513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a transdiagnostic psychodynamic online intervention to support return to work: A randomized controlled trial

Abstract: ObjectivesGiven their flexibility, online interventions may be useful as an outpatient treatment option to support vocational reintegration after inpatient rehabilitation. To that purpose we devised a transdiagnostic psychodynamic online intervention to facilitate return to work, focusing on interpersonal conflicts at the workplace often responsible for work-related stress.Research design and methodsIn a randomized controlled trial, we included employed patients from cardiologic, psychosomatic and orthopedic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 40 publications
0
16
0
8
Order By: Relevance
“…The majority of interventions ( n = 11) were based on principles of Cognitive Behavioral Therapy (CBT). One study ( Bischoff et al, 2013 ) was based on general psychotherapy ( Grawe, 1997 ), two studies on psychodynamic ( Zwerenz et al, 2017a ; Zwerenz et al, 2017b ) and one on mindfulness-based cognitive therapy (MBCT) ( Kraft et al, 2017 ) or focused on disease management ( Välimäki et al, 2017 ). Eleven IMIs were web- and 5 predominantly mobile-based.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of interventions ( n = 11) were based on principles of Cognitive Behavioral Therapy (CBT). One study ( Bischoff et al, 2013 ) was based on general psychotherapy ( Grawe, 1997 ), two studies on psychodynamic ( Zwerenz et al, 2017a ; Zwerenz et al, 2017b ) and one on mindfulness-based cognitive therapy (MBCT) ( Kraft et al, 2017 ) or focused on disease management ( Välimäki et al, 2017 ). Eleven IMIs were web- and 5 predominantly mobile-based.…”
Section: Resultsmentioning
confidence: 99%
“…Study dropout varied between 5.6% ( Fichter et al, 2012 ) and 64.2% ( Bischoff et al, 2013 ) with an average of 26.3%. About two third of the studies included passive CGs, one-third active CGs ( Bischoff et al, 2013 ; Holländare et al, 2011 ; Zwerenz et al, 2017a ; Zwerenz et al, 2017c ). The majority of studies ( n = 10) reported at least a medium follow-up period (6–12 months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online programs have been used successfully to prevent relapse in patients with remitted depression [20,21,22] following outpatient or inpatient psychotherapy or rehabilitation in order to maintain treatment gains in recent trials [23,24]. However, we are not aware of a trial examining the efficacy of an online self-help program in addition to inpatient psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Eines der wenigen Online-Programme mit psychodynamischem Hintergrund ist das am Universitätsklinikum Mainz entwickelte "Gesundheitstraining Stressbewältigung am Arbeitsplatz-online" (GSA-online [9]). Das Programm basiert auf einem supportiv-expressiven, schreibtherapeutischen Ansatz und soll Patienten nach der stationären psychosomatischen Rehabilitation bei der beruflichen Wiedereingliederung unterstützen.…”
Section: Gesundheitstraining Stressbewältigung Am Arbeitsplatz Onlineunclassified